The Barroso Research lab: biomolecular interactions, computing, and data-driven science to understand and engineer biological and pharmaceutical systems in a global academic partnership - Barroso da Silva, Fernando L.; Etchebest, Catherine; E. Santiso, Erik; Corrêa Giron, Carolina; Grandguillaume, Ilyas; Borges Marques, Rauni; Poveda-Cuevas, Sergio A. (Journal of Information and Data Management, 2024)
Biomolecular interactions, high throughput computing, and data-driven science have been the central research foundations of the Barroso Research laboratory. We have been developing and applying innovative computational technology, offering a rational computational-based approach to the investigation of protein systems, and discovering key disease-related protein mechanisms, therapeutic agents, biomarkers, and proteins for specific applications and their controlled release. Born in 2001 at the School of Pharmaceutical Sciences at Ribeirão Preto with the genes of transdisciplinary and internationalization, the laboratory has always been well integrated with research groups in Europe, the US, and Latin America. Students from different fields and places have been forged in this environment at the crossroads of Structural Bioinformatics, Molecular Biophysics, Biological Physics, Physical Chemistry, Engineering, Medicine, Food, and Pharma. The more than 50 scientific papers published in high-impact journals, book chapters, and conference talks reflect our contributions to expanding knowledge and advancing Bioinformatics as an important tool to understand nature and guide innovations.